Service-oriented architecture an integration blueprint : a real-world SOA strategy for the integration of heterogeneous enterprise systems - Schmutz, Guido; Liebhart, Daniel; Welkenbach, Peter (Professional expertise distilled, 2010)
"The book begins by covering fundamental integration for those less familiar with the concepts and terminology, and then dives deep into explaining the different architecture variants and the future of integration technologies. Base technologies like JCA and SCA will be explored along the way, and the structure of the Trivadis Integration Architecture Blueprint will be described in detail, as will the intricacies of each component and layer. Other content includes discovering and comparing traditional and modern SOA driven integration solutions, implementing transaction strategies and process modeling, and getting to grips with EDA developments in SOA. Finally, the book considers how to map software from vendors like Oracle and IBM to the blueprint in order to compare the solutions, and ultimately integrate your own projects successfully."--Resource description page.